2021
DOI: 10.1177/23259671211028168
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and Randomized Clinical Evaluation of Hamstring Versus Patellar Tendon Autograft for Anterior Cruciate Ligament Reconstruction in Soccer Players

Abstract: Background: Anterior cruciate ligament (ACL) reconstruction is usually performed with autologous bone–patellar tendon–bone (PT) or hamstring tendon (HT) graft. There has been only 1 randomized clinical trial examining ACL reconstruction with these grafts specifically in soccer players, and more studies comparing these graft types within a homogenous cohort such as soccer athletes may better highlight differences in outcomes. Purpose: To compare the results of ACL reconstruction with PT versus HT autograft in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It has been reported that the long period of healing in the interzone between bone tunnel and graft makes up one of the factors to delay the return to pre‐injury activity, and there is also an existent relationship between harvest site healing time and anterior knee pain. 4 , 5 , 6 Though the treatment role of PRP in ACL‐reconstructed patients has not been definitely identified, it has been applied with the anticipation of accelerating the recovering processes. In many former cytological, histological or biomechanical studies, PRP was shown to have positive effects on promoting tendon healing at the injured site by promote cell proliferation and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the long period of healing in the interzone between bone tunnel and graft makes up one of the factors to delay the return to pre‐injury activity, and there is also an existent relationship between harvest site healing time and anterior knee pain. 4 , 5 , 6 Though the treatment role of PRP in ACL‐reconstructed patients has not been definitely identified, it has been applied with the anticipation of accelerating the recovering processes. In many former cytological, histological or biomechanical studies, PRP was shown to have positive effects on promoting tendon healing at the injured site by promote cell proliferation and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Additionally, the slow healing process of defect at harvest site has been recognized as a cause of persistent anterior knee pain even after many years. 6 Although the treatment role of platelets‐rich plasma (PRP) remains unclear, it has been provided with the aim of accelerating the maturation of the graft and healing processes of bone tunnel and donor site. 7 Theoretically, after applying of PRP to the ACL‐reconstructed patients, a myriad of growth factors (GFs) and proteins would be released to the local environment, which could potentially accelerate the tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guglielmetti reported the same result in his ACL reconstruction using metal interference screws. The mean Lysholm score of the patellar tendon group was 89.87 points (range, 65-100), and that of the hamstring tendon group was 91.26 points (range, 60-100) at 2 years post-operation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey study of members of the American Orthopaedic Society for Sports Medicine (AOSSM) and Arthroscopy Association of North America (AANA), the second most important factor for graft selection was graft failure rates reported in the literature [6]. However, the current evidence on re‐rupture/revision rates between two of the most frequently used grafts, hamstring (HT) autografts and bone–patellar tendon–bone (BTB) autografts, is conflicting [2, 3, 5, 9, 10, 12, 14, 16–18, 20, 22, 34–36, 39, 41, 43, 46]. For example, Samuelsen et al performed a meta‐analysis which demonstrated a significantly lower re‐rupture rate among BTB autografts ( P = 0.01), whereas a meta‐analysis from Mouarbes et al showed no significant difference in re‐rupture rates between these two graft types (n.s.)…”
Section: Introductionmentioning
confidence: 99%